Seeking Relevant Biomarkers in Common Variable Immunodeficiency - Ho, Hsi-en; Cunningham-Rundles, Charlotte (Frontiers in Immunology, 2022)
Common variable immunodeficiency (CVID) is the most common symptomatic form of primary immunodeficiency. More than 50% of patients in some series suffer from autoimmune or inflammatory complications (the “CVID+” phenotype), and these are not adequately addressed by current treatments. Despite significant advancements in genetics, the pathogenesis of the CVID+ phenotype has remained unexplained for most patients, necessitating the need for relevant biomarkers in both the clinic and research settings. In the clinics, reduced isotype-switched memory B cells (≤ 0.55% of B cells) and reduced T cells (CD4) can be utilized to identify those with increased complication risks. Additionally, condition-specific markers have also been suggested for lymphoma (normal or elevated IgM) and progressive interstitial lung disease (increased BAFF, normal or elevated IgM). Additional biomarkers have provided insights into disease pathogenesis, demonstrating wider systemic inflammation (increased LBP, sCD14, and sCD25; expanded ILC3), mucosal defects (increased zonulin, I-FABP), and perhaps reduced anti-inflammatory capability (reduced HDL) in CVID. Most recently, efforts have revealed elevated circulating bioactive bacterial DNA levels – marking microbial translocation and potentially unifying the causation of multiple inflammatory changes previously observed in CVID. The implementation of high throughput profiling techniques may accelerate the search of relevant biomarker profiles in CVID and lead to better clinical risk stratification, revealing disease insights, and identifying potential therapeutic targets.